2021
DOI: 10.7759/cureus.16901
|View full text |Cite
|
Sign up to set email alerts
|

Volume-Staged Radiosurgery for Large Arteriovenous Malformation: Retrospective Analysis of 19 Cases

Abstract: Introduction The effectiveness of Gamma Knife surgery (GKS) for small arteriovenous malformations (AVMs) is well known. However, for large AVMs, the prescribed dose should be decreased to reduce the risk of radiation damage, but it leads to a decrease in nidus obliteration rates. Therefore, it is very difficult to achieve complete obliteration of large AVMs in a single treatment, and methods using multiple irradiation such as volume-staged stereotactic radiosurgery (VS-SRS) have been suggested. We r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
1
1
Order By: Relevance
“…However, RICs were developed in 36 patients (72%) after single-session GKRS. The previous studies proposing the volume-staged GKRS for large AVMs reported the obliteration rate of 58.2% 32 and 62.5% 33 with AVMs >10 cc, which was superior to this study including only single-session GKRS. Further studies with more volume-stage cases and longer follow-up are necessary to confirm the effectiveness and safety of volume-staged GKRS.…”
Section: Discussioncontrasting
confidence: 75%
“…However, RICs were developed in 36 patients (72%) after single-session GKRS. The previous studies proposing the volume-staged GKRS for large AVMs reported the obliteration rate of 58.2% 32 and 62.5% 33 with AVMs >10 cc, which was superior to this study including only single-session GKRS. Further studies with more volume-stage cases and longer follow-up are necessary to confirm the effectiveness and safety of volume-staged GKRS.…”
Section: Discussioncontrasting
confidence: 75%
“…In that case, volume-staged SRS is considered to be more favorable than dose-staged SRS regarding obliteration rates. [43][44][45] Marginal doses ranging from 15 to 20 Gy in two to four stages should be delivered to achieve obliteration, 44,45) although caution should be focused on adverse effects.…”
Section: Obliterationmentioning
confidence: 99%